Are fire safe cigarettes actually fire safe? Evidence from changes in US state laws. Issue 3 (19th June 2017) - Bonander, Carl; Jakobsson, Niklas; Nilson, Finn
Abstract : Objective: To estimate the effects of fire safe cigarette laws on fire mortality and cigarette-related fires in the USA. Methods: We examined the gradual implementation of the laws to identify their average effects, using difference-in-differences analysis to account for common year effects, time-invariant state effects, state-specific trends and observable time-varying state-level covariates. Results: We found no statistically significant effects on all-cause fire mortality, residential fire mortality or cigarette-caused fire rates. The estimates for cigarette-caused fire deaths were significant under some specifications, but were not robust to the inclusion of state-specific trends or comparisons to effects on other cause-determined fires. Conclusions: Given the mixed state of our results, we conclude that previous claims regarding the effects of fire safe cigarette laws may be premature.